Geochemical associations between fluorite mineralization and A-type shoshonitic magmatism in the Keban-Elazig area, East Anatolia, Turkey - Akgul, Bunyamin (Pergamon-Elsevier Science Ltd, 2015)
Keban fluorite mineralizations are closely related Coniacian-Campanian subvolcanics intruded into Permian-Triassic Keban metamorphites; this event caused pyrometasomatic, porphyry, and vein-type Pb-Zn-Ag, Cu, W, and Pb-Zn-Ag-Mo-F mineralizations. These rocks are syenitic and syenomonzonitic in composition and have high Al2O3, alkali (Na2O + K2O), FeO*/MgO, Zr, Nb, Ta, Ga, Rb, Y, and rare earth element (REE) contents. They are A-type, metaluminous, and all fall in the shoshonitic series field in K2O vs SiO2 and Th/Yb vs Ta/Yb diagrams. The trace element contents and discriminations indicate that the Keban syenitoids were derived from lithospheric mantle metasomatized by oceanic-crust/sediment fluids. The metal and halogen contents of the Keban mineralizations apparently originated from metasomatized mantle and were transported to the crust by syenitoid magmas. Clear resemblances in chondrite-normalized REE patterns, LREE-HREE partionation, and high LILE contents of the magmatics and fluorites indicate a close kinship between the syenitoids and fluorite mineralizations. The HFSE contents of the fluorites are lower than those of the magmatics, as HFSEs are not soluble in aqueous fluids. The fluorites are products of early-phase alkali magmatism (LREE > HREE). The high contents of Rb, Sr, and Ba of fluorites are inherited from the magma, which also has very high contents of these elements. In Se-Sigma REE, (La/Yb)(n)-(Eu/Eu*)(n) and (Tb/La)(n)-(Tb/Ca)n diagrams, Keban fluorites fall into distinct areas from Akcakisla-Akdagmadeni and Celikhan-Adiyaman fluorites. (C) 2015 Published by Elsevier Ltd.
Keywords: Fluorite; Syenitoid; Shoshonite; REE; Keban; Turkey